Caregiver self-care and care of the elderly - Wanda Pereira Patrocinio (Kairós Gerontologia, 2016)
This article aims to discuss on the task of caring for the elderly and the implications for families and professionals. In the first part we will discuss the need for adequate caregiver training. In the second part we will present activities for the caregiver self-care and other based on the National Integrative and Complementary Practices Policy. Finally, we will expose activities that the caregiver can develop for care of the elderly. It is expected that these activities may contribute to the quality of life of caregivers, as well as a better performance of its function.